The Role of Advertising and Word of Mouth in Promoting Destination Brand Equity of Isfahan - Amin Ajali (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2014)
The word-of-mouth (WOM) and non-conversational advertising are two well-established methods to attract tourists to destinations. Since the tourism product is mostly untestable before it is used, the role of advertisement is fortified. Consequently, the present research explores the impact of conversational and non-conversational advertising on promotion of brand equity in the touristic city of Isfahan. A questionnaire survey was conducted on a sample of 384 potential tourists to Isfahan. Data were analyzed through SEM and CFA by making use of SPSS and LISREL softwares. Results demonstrated that advertisement had no significant bearing on the destinations’ brand image, while at a 99 percent confidence level, WOM and customer experience showed a significant effect. Also, a significant impact was found exerting from conversational and non-conversational advertisement on customer experience. Customer experience itself influences brand equity, and the brand image affects destination brand equity, all at a 99 percent confidence level.